Supressão de plantas daninhas utilizando plantas de cobertura do solo - Borges, W. L. B. (2014)
This study aimed to evaluate soil cover and the suppressive effect on weeds by different cover crops at different seed densities. The experiments were set up in Votuporanga, state of Sao Paulo, Brazil and in Selviria, state of Mato Grosso do Sul, Brazil, in March 2008, after conventional tillage. The experimental design was a randomized complete block with four replications, using the following cover crops at different seed densities per hectare: Sorghum bicolor: 6, 7 and 8 kg ha(-1), Pennisetum americanum, 10, 15 and 20 kg ha(-1), Sorghum sudanense, 12, 15 and 18 kg ha(-1), hybrid of Sorghum bicolor with Sorghum sudanense: 8, 9 and 10 kg ha(-1), Urochloa ruziziensis: 8, 12 and 16 kg ha(-1). A control treatment with spontaneous vegetation was used. Soybean was sown after the management of cover crops. Dry matter and weed density were evaluated at cutting/harvesting of cover crops. In Votuporanga, another assessment of weed plants was made at 35 days after soybean had been sown. The ground cover provided by cover crops was assessed at the time of desiccation and flowering of soybeans. It was concluded that U. ruziziensis and S. sudanense reduced weed infestations by more than 90% and kept ground cover above 80% by the time of flowering of soybean.